2023
DOI: 10.24018/ejmath.2023.4.1.208
|View full text |Cite
|
Sign up to set email alerts
|

Hermite Interpolation Approach to High-Order Approximation of Heat Equations

Abstract: It is usually desirable to approximate the solution of mathemati- cal problems with high-order of accuracy and preferably using com- pact stencils. This work presents an approach for deriving high-order compact discretization of heat equation with source term. The key contribution of this work is the use of Hermite polynomials to reduce second order spatial derivatives to lower order derivatives. This does not involve the use of the given equation, so it is universal. Then, Tay- lor expans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The present work extends the work in [8] by investigating the performance of nine fixed point methods with regards to their computational costs on five nonlinear integral equations. In section 2, we present the nine discrete fixed point iteration schemes for solving (1)- (2).…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…The present work extends the work in [8] by investigating the performance of nine fixed point methods with regards to their computational costs on five nonlinear integral equations. In section 2, we present the nine discrete fixed point iteration schemes for solving (1)- (2).…”
Section: Introductionmentioning
confidence: 77%
“…This method is represented as if it has three operator evaluations but it actually has only two. This is why recent study [8] has found that the schemes of Argawal and coworkers and that of Ishikawa have approximately equal efficiency and even accuracy. Noor [9] proposed a three-step method with three operator evaluations, see also [10] for another such method.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations